Hemoglobinopathies in pregnant women submitted to the mommy test in the Brazilian public health network - Liberato, Keesi Marcela Matos; Oselame, Gleidson Brandão; Neves, Eduardo Borba (Journal of Health Care, 2017)
Introduction: The hemoglobinopathies are among genetic diseases of great importance in the world. Approximately 7% of the global population have some kind of hemoglobinopathy, and estimates show that about 300,000 to 400,000 children affected by these disorders are born each year. Objective: To describe prevalent diagnoses of hemoglobinopathies in pregnant women submitted to the Mommy Test in the Brazilian public health network. Methods: Cross-sectional, descriptive study with quantitative analysis of the data. The sample included 1,013 electronic medical records of pregnant users of the public health network of the municipality of Pinhais, state of Paraná, Brazil, recorded between February 25th, 2014 and February 25th, 2015. Medical records of pregnant women undergoing up until the third quarter of pregnancy submitted to the Mommy Test were used. Results: It was observed that 55.7% of the pregnant women were submitted to the Mommy Test in their first quarter. Only 0.7% of the results of the test showed the Hemoglobin C trait, and 1.3% presented sickle cell trait. As for race, in the results that showed alterations (n=20), 50% of the women were white, 40% were brown, and 10% were black. Among these participants, 80% presented intercurrences during the pregnancy, the most frequent being urinary tract infection (50%), general leucorrhea (25%), and intercurrences during delivery (12.5%). Conclusion: A low prevalence of hemoglobinopathies was observed in this study. The implementation of the Mommy test in the Brazilian public health network is recommended for early diagnosis of gestational hemoglobinopathies.